Analysis of the Use of Infographic Media in Teaching Procedural Texts to Enhance Students’ Learning Motivation in Grade 9 at SMPN 6 Kota Cirebon - reyhan, ahmad (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
his study aims to analyze the use of infographic media in teaching procedural texts as an effort to enhance the learning motivation of Grade 9A students at SMPN 6 Kota Cirebon. Infographics were chosen for their ability to visually present information in an engaging way, which is expected to facilitate understanding and increase students’ interest in learning. The research employed a qualitative approach, with data collected through observations and interviews. The findings indicate that the use of infographic media in procedural text learning can enhance students’ learning motivation. This is evidenced by increased student enthusiasm during the learning process. Teachers also reported that infographics helped simplify complex material, making it easier for students to understand. However, several challenges were noted, such as students' difficulty in conceptualizing ideas for their infographics and technical issues related to internet access. Overall, the use of infographics proved effective in improving both students’ motivation and understanding in procedural text learning.